O Judiciário e a incorporação de tecnologias em saúde: uma análise de decisões sobre concessão de fármacos não incorporados ao SUS sob o paradigma da Crítica Hermenêutica do Direito - Faria, Lucas Oliveira (2023)
Health judicialization is a growing reality in Brazil that, ultimately, may represent the Judicial Power as an way to ensure the health fundamental right effectiveness, and might become an undue intervention capable of provoking unwanted budget deallocation and, even further, compromising the public politics execution of public health, causing judicial activism. Due to the persistent judicial interventions in public health matters, CONITEC (National Commission for the Incorporation of Technologies into the Unified Health System, also known as SUS) was established by Federal Law n. 12.401/2011, which lays out about therapeutics assistance and technology incorporation into the health public system. CONITEC is responsible for recommending to the Health Ministry the incorporation, exclusion, or alteration, within SUS, of the National List of Essential Medicines (RENAME), in other words, the medicines that must be provided to the population due to the system. As widely known, there are countless technological innovations in healthcare, mainly due to the post-modern concept of increasing life expectancy. This is why CONITEC is frequently tasked with evaluating the incorporation of new drugs into SUS. This study aims to analyze decisions made by the São Paulo State Court that compels the State to provide the population with medications not included in SUS due to administrative decisions based on CONITEC recommendations, drawn from the theoretical contribution of Hermeneutic Critique of Law, focused on cases adjudicated in Ribeirão Preto City, State of São Paulo, between 2020 and 2022, using a hermeneutic approach method from an inductive perspective, and data collection method through documental and bibliographical research, in addition to jurisprudential research with a qualitative perspective through content analysis. The study's intention is to clarify whether, in the analyzed cases, it is possible to conclude whether the expected phenomenon of health judicialization occurs or if there is the unwanted misunderstanding of judicial activism. The conclusion is that judicial decisions do not satisfy the argumentative burden imposed by the Hermeneutic Critique of Law on judicial intervention in social fundamental rights, disregarding completely the existence of the legally established health technology evaluation system, asserting a conception of the fundamental right to health that encompasses any drug prescribed by a M. D., thus becoming a severe example of judicial activism.